2013
DOI: 10.1007/s12011-013-9789-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China

Abstract: Sediments from 14 stations in the Foshan Waterway, a river crossing the industrial district of Guangdong Province, South China, were sampled and subsequently analyzed. The 14 stations were selected for the pollution discharging features of the river, such as the hydrology, the distribution of pollution sources, and the locations of wastewater outlets. The ecological risks were assessed, and the pollution sources were identified to provide valuable information for environmental impact assessment and pollution c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…The samples were diluted to 50 ml with Milli‐Q water (Millipore, Bedford, MA) in 50‐ml‐volume tubes. After dilution and filtration using Whitman filter paper 1, the digested samples were analysed by atomic absorption spectrophotometry (AAS) according to the method described by Li et al () and Pakshirajan, Worku, Acheampong, Lubberding, and Lens ().…”
Section: Methodsmentioning
confidence: 99%
“…The samples were diluted to 50 ml with Milli‐Q water (Millipore, Bedford, MA) in 50‐ml‐volume tubes. After dilution and filtration using Whitman filter paper 1, the digested samples were analysed by atomic absorption spectrophotometry (AAS) according to the method described by Li et al () and Pakshirajan, Worku, Acheampong, Lubberding, and Lens ().…”
Section: Methodsmentioning
confidence: 99%
“…In aquatic systems, sediments are the main sink of various contaminants discharged from industrial and agricultural processes [5][6][7], and they are regarded as an effective archive recording heavy metal contamination [2,8,9]. To date, a large number of studies have reported the accumulation of heavy metals in the sediments of aquatic ecosystems [3,[10][11][12][13]. The main reason is that once the conditions of sedimentary environment change, heavy metals are apt to release into water from the sediments [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, various methods have been applied to assess the contamination and ecorisk of heavy metals in sediments, including enrichment factor [31,32], index of geoaccumulation [33,34], toxic units and toxic risk index [35], and potential ecorisk index [22,36]. However, each method has its limitation or specialization, and thus it is necessary to use multiple methods in order to accurately obtain the contamination and ecorisk states of heavy metals in sediments [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing soils pollution caused by heavy metals (HMs), due to agricultural and industrial activities, is becoming a serious environmental problem to the present world (Li et al, 2013;Imran et al, 2015). The direct and indirect discharges of industrial and urban wastes have resulted in the chemical contamination of the soil by organic pollutants and HMs (Sun et al, 2012;Elloumi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%